2019
DOI: 10.21303/2504-5695.2019.001066
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Fomitopsis Betulina Cultural Liquid

Abstract: The antibacterial activity of Fomitopsis betulina cultural liquid (native, native concentrated, lyophilized, dried) against standard bacteria (Escherichia coli АТСС 25922, Pseudomonas aeruginosa АТСС 27853, Staphylococcus aureus АТСС 25923), and clinical isolates (Acinetobacter baumannii 50/1496 MBL, A. baumannii 88/2995 MBL, E. coli 116/3196 KPC, Klebsiella pneumoniae 6/509 ESBL, AmpC, KPC, P. aeruginosa 99/3066 MBL, P. aeruginosa 125/3343 MBL, S. haemoliticus 22/824 MRSA, S. aureus 134/3569 MRCNS) has been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In addition, the astringent effect alone makes it good for making mushroom-containing herb tea or an immune tonic to be taken once a week to boost the immune system. F. betulina contains primary metabolites (as polysaccharides) and secondary metabolites (as triterpenes) that are beneficial for health [ 6 , 143 , 222 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the astringent effect alone makes it good for making mushroom-containing herb tea or an immune tonic to be taken once a week to boost the immune system. F. betulina contains primary metabolites (as polysaccharides) and secondary metabolites (as triterpenes) that are beneficial for health [ 6 , 143 , 222 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Yim et al, [3] this fungus can be found in both sub-tropical and tropical woods. It is frequently used as a food ingredient, particularly in Asian nations because it contains nutrients that are good for the body like protein, fiber, and carbohydrates Krupodorova & Barshteyn, [4]. Additionally, S. commune extract has the ability to treat diseases caused by bacteria and fungi, making it a potential antibacterial agent, according to Mirfat et al [5].…”
Section: Introductionmentioning
confidence: 99%